(3QSGdI eGQjI HfJ SGHI Gdedc GdbHWi Edi (B" (3CQS(B" (3hSDGdg hLhGHgG dgs
(3BNQgG (B:s
(3GeJRL CMLGQ GdUfYI GdCQHYI hbHhd HYVgG dHYV hCdhGfgG EPG CeJRLG ceG hUafG dc Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B41 - (3U(B42s
(3GdfSNI HgG MhGTs
(3jdjgG ahGFO hfbhd eNJdaI ai Yde GdcjejGA efbhdI Yf GdWZQGFi hPi Gdfhf hGdeLQjWi hLGHQ Hf MjGf ef cJGH GdUhaI hGdMcje GdChRYi ef cJGHg GdOQ Gdecfhf ai eHGbd GdMLQ GdeUhfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdcjejGA h GdWHjYjGJs